Монгол орны шилний элсний судалгаа - М. Цэрэнчимэд (Scientific transaction of the National University of Mongolia. Physics, 2022)
Abstract: Series of laboratory experiments to melt glass from sand have been completed in Gorkhi pegmatit crystal deposit, Zuun mod deposit, Central province, Altangol, Buirnuur deposit, Dorot province, Boruruu deposit, Sukhbaatar province. The glass and glass properties have been identified jointly with the researchers of the Glass and Ceramics Laboratory BAM, Germany. The investigation of physical properties of sand and glass has been performed applying chemical analysis, liquid gas extraction, ESR study, infrared radiation and dilatometric research using sophisticated equipment and techniques. It is revealed and concluded that sand from all deposits except Zuunmod deposit, Central province can melt transparent, high quality glass.